Modified Thrombolysis in Cerebral Infarction 2C/Thrombolysis in Cerebral Infarction 3 Reperfusion Should Be the Aim of Mechanical Thrombectomy: Insights From the ASTER Trial (Contact Aspiration Versus Stent Retriever for Successful Revascularization). Issue 5 (May 2018) - Dargazanli, Cyril; Fahed, Robert; Blanc, Raphael; Gory, Benjamin; Labreuche, Julien; Duhamel, Alain; Marnat, Gaultier; Saleme, Suzana; Costalat, Vincent; Bracard, Serge; Desal, Hubert; Mazighi, Mikael; et al.
Abstract : Background and Purpose—: Although successful reperfusion is usually defined as a modified Thrombolysis in Cerebral Infarction (mTICI) 2B or 3 at the end of the procedure, studies have shown that mTICI 2B patients had poorer functional outcomes than TICI 3 patients. An mTICI 2C category has been recently introduced for patients with near-complete perfusion except for slow flow in a few distal cortical vessels or presence of small distal cortical emboli after mechanical thrombectomy. The purpose of this study was to evaluate the difference in functional outcome between patients achieving successful reperfusion (ie, mTICI 2B, mTICI 2C, and TICI 3 scores). Methods—: Ancillary study from the ASTER (Contact Aspiration Versus Stent Retriever for Successful Revascularization) prospective multicenter blinded end point trial. Reperfusion results are reported as the mTICI score, including the mTICI 2C grade. Primary outcome was the percentage of patients with favorable outcome defined as a 90-day modified Rankin Scale score of 0 to 2. Results—: Two hundred ninety patients with successful reperfusion (mTICI ≥2B), harboring ischemic stroke secondary to occlusion of the anterior circulation within 6 hours of onset of symptoms, undergoing mechanical thrombectomy by contact aspiration or stent retriever were included. Favorable outcome (pre-specified as primary outcome of this ancillary study) did not differ significantly between the 3 reperfusion grades, with a similar positive effect of 2C (odds ratio, 1.71; 95% confidence interval, 0.98–3.00) and 3 (odds ratio, 1.73; 95% confidence interval, 0.88–3.41) grades compared with 2B grade. After combining grades 2C and 3, patients had a significantly higher rate of favorable outcome than patients with 2B (odds ratio, 1.72; 95% confidence interval, 1.01–2.90; P =0.043). Favorable outcome rate decreased with increasing onset-to-reperfusion time, with no significant interaction between mTICI 2C/3 grade and onset-to-reperfusion time on favorable outcome. Conclusions—: Combining mTICI 2C and TICI 3 grades helps to determine a subgroup of patients achieving better functional outcomes than mTICI 2B patients. Achieving mTICI 2C/3 reperfusion should be the new aim of mechanical thrombectomy for anterior circulation LVO. Abstract : Supplemental Digital Content is available in the text.